The Impact of Task-Based Language Teaching (TBLT) Method on Students' Speaking Ability at Senior High School - Lili, Reski; Sujarwo, Sujarwo; Ibrahim, Muliaty; Yahrif, Muhamad (Universitas Cokroaminoto Palopo, 2025)
Much research has shown that task-based language learning (TBLT) can improve students' speaking ability. However, many students struggle to speak, especially at the senior high school level. This research aimed to determine the impact of the Task-Based Language Teaching (TBLT) method on the speaking ability of SMA Negeri 14 Gowa class XI students. The design of this research used an experimental procedure with a quantitative approach. The population of this research was 62 students who were divided into two classes, namely the control class and the experimental class. This research used pre-tests and post-tests. Then, the researcher continued with four meetings using the task-based language teaching method (TBLT). This data was obtained through pre-test and post-test, where the researcher took the students' speaking performance scores. The results showed that the average pre-test score of students in the control class was 58.45, and the post-test was 59.87. While the average pre-test score in the experimental class was 58.71, and the post-test was 70.32. There was a significant difference in the average score in the experimental class. The value increased by 11.6, after being given treatment with a significance level of 0.004 <0.05, H0 was rejected and Ha was accepted. Based on the results of this research, it can be concluded that there is an improvement in students' speaking ability using task-based language Teaching in class XI IPA I students of SMA Negeri 14 Gowa Keywords Task-Based Language Teaching (TBLT) Method, Sharing Personal Experience, Speaking Ability